Formation and development of the production potential of the enterprise - Михайленко, Ольга (SWorldJournal, 2020)
The article highlights the main issues of management actions that are the basis and / or the result of the formation and development of the production potential of the enterprise. The author summarizes the approaches to the study of the essence of the pot